What’s inside the net? insights into fish bycatch diversity in the Antarctic krill fishery - María Lorena Romero Martínez; William D. K. Reid; Martin A. Collins; Katia Lizeth Treviño Cuellar; William P. Goodall-Copestake; James M. Clark; Benedict Viney; Susan Gregory; Kate Owen; Philip R. Hollyman (Polar Biology, 2026)
An ecosystem-based approach to fishery management requires, inter alia, knowledge of fishery impacts on both target and non-target species, as well as the wider ecosystem. To support management of the Antarctic krill fishery, we present a robust reference dataset for identifying fish species caught as bycatch. By combining morphological and molecular taxonomic identification, 53 fish species in 44 genera and 11 families were confidently identified. Our dataset extends the DNA barcode library of Sub-Antarctic and Antarctic fish species and provides a foundation for developing an enhanced identification guide for larval fish to be used by observers on board krill fishing vessels. Phylogenetic relationships were inferred from two commonly used barcode markers, the mitochondrial cox1 and the non-coding control region. We observed clear phylogenetic relationships, highlighting coherent placements of notothenioids, myctophids, Aulopiformes, Gadiformes and Zoarcoidei. The results suggest a discrepancy between observer-based and genetic identifications, with 20.6% of records representing misidentifications in the fishing seasons 2021/2022 and 2022/2023. Graphical Abstract Graphical abstract: illustrated by ©Louise Merquiol-Hatsya illustrations

Patagonian deglaciation: aquatic macroinvertebrate biodiversity in proglacial and paraglacial ponds - Matthew Hill; Ryan Wilson; Luis Uribe; Brian Reid; Pablo Pedreros; Paul J. Wood; Kate L. Mathers (Biodiversity and Conservation, 2026)
Glacier retreat is rapidly transforming cryospheric landscapes with new pond networks establishing in deglaciated landscapes. However, our understanding of the aquatic biodiversity within these rapidly evolving landscapes has been limited, especially in southern Patagonia despite having the largest temperate icefields globally. We examined the aquatic macroinvertebrate diversity in paraglacial forest and proglacial ponds at the snout of the Exploradores Glacier (Southern Patagonia, Chile) and assessed the environmental factors influencing taxonomic richness and community composition. Alpha and estimated gamma diversity were significantly higher in periglacial forest ponds compared to proglacial ponds. Clear differences in macroinvertebrate community composition were recorded between paraglacial and proglacial ponds. Taxonomic turnover explained most of the variation in community composition with Trichoptera and Diptera taxa constituting a greater proportion of taxonomic richness in proglacial ponds, while Coleoptera and Hemiptera taxa represented a higher proportion of taxa in paraglacial forest than proglacial ponds. When taxa-environment relationships were examined, a significant negative association was recorded between dissolved oxygen and taxonomic richness. Sodium concentrations were also found to be negatively associated with LCBD. This study provides vital evidence that ponds formed naturally due to deglaciation can support a wide diversity of aquatic macroinvertebrates, and as glacial retreat continues and landscapes transition from glacial to paraglacial, pond habitats represent increasingly important freshwater habitats at the landscape scale. Future research is critical to advance understanding of proglacial and paraglacial pond networks to provide the underpinning information needed to raise awareness to support the conservation of these unique habitats.

Native trees are related to advanced bird breeding phenology and increased reproductive success along an urban gradient - Claire J. Branston; Pablo Capilla‐Lasheras; Conor Haugh; Paul J. Baker; Rachel Reid; Kate Griffiths; Stewart White; Davide M. Dominoni (Ecology, 2026)
Urban areas are altered from natural landscapes in several ways that can impact wildlife. Birds are widespread in urban areas, and it is well documented that there are phenotypic differences between urban and non‐urban conspecifics. However, little is known about which characteristics of the urban environment are driving differences. We used 9 years of data from nest boxes spread across 20 sites along a 40‐km urban–non‐urban gradient in Scotland to test whether characteristics of the urban environment (native, non‐native, native oak ( Quercus spp.), birch ( Betula spp.) foliage availability, temperature and human population density, and the interaction between foliage and temperature) influenced phenology and reproductive success in blue tits ( Cyanistes caeruleus ). We found that higher foliage availability of native foliage, and specifically of the most common native genus, oak, was associated at the territory level with earlier first egg laying date. Higher non‐native foliage availability at both a site and territory level was negatively related to clutch size. The number of fledglings produced was reduced at sites with higher levels of non‐native foliage and increased at sites with greater amounts of native oak foliage present. We also found territories with a higher human population density had reduced fledging success. Temperature was negatively related to first egg laying date, clutch size and the number of fledglings produced. Moreover, the number of Lepidopteran larvae, blue tits' preferred prey, that were collected over the breeding season was positively related to native oak foliage availability. Our results strongly indicate that the presence of native trees, such as oak, are beneficial to breeding insectivores by increasing the number of fledglings they can successfully raise, likely due to the increased availability of invertebrate prey. We suggest that urban planting regimes should be carefully considered, selecting tree species that are native or non‐native congeneric species, and most importantly that will host Lepidoptera larvae. This will not only help to support complete food chains, but also to maximize biodiversity and ecosystem services of urban green spaces.

Do environmental attitudes and personal characteristics influence how people perceive their exposure to green spaces? - Emma S. Rieves; Colleen E. Reid; Kate Carlson; Xiaojiang Li (Landscape and Urban Planning, 2024)

Supporting each other: Older adults’ experiences empowering food security and social inclusion in rural and food desert communities - Rebecca Davies; Kate Reid (Appetite, 2024)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

A will-o’-the wisp? On the utility of voluntary contributions of data and knowledge from the fishing industry to marine science - Nathalie A. Steins; Steven Mackinson; Stephen C. Mangi; Martin A. Pastoors; Robert L. Stephenson; Marta Ballesteros; Kate Brooks; James A. McIsaac; Matthew R. Baker; Julia Calderwood; Barbara Neis; Emily M. Ogier; et al. (Frontiers in Marine Science, 2022)
For future sustainable management of fisheries, we anticipate deeper and more diverse information will be needed. Future needs include not only biological data, but also information that can only come from fishers, such as real-time ‘early warning’ indicators of changes at sea, socio-economic data and fishing strategies. The fishing industry, in our experience, shows clear willingness to voluntarily contribute data and experiential knowledge, but there is little evidence that current institutional frameworks for science and management are receptive and equipped to accommodate such contributions. Current approaches to producing knowledge in support of fisheries management need critical re-evaluation, including the contributions that industry can make. Using examples from well-developed advisory systems in Europe, United States, Canada, Australia and New Zealand, we investigate evidence for three interrelated issues inhibiting systematic integration of voluntary industry contributions to science: (1) concerns about data quality; (2) beliefs about limitations in useability of unique fishers’ knowledge; and (3) perceptions about the impact of industry contributions on the integrity of science. We show that whilst these issues are real, they can be addressed. Entrenching effective science-industry research collaboration (SIRC) calls for action in three specific areas; (i) a move towards alternative modes of knowledge production; (ii) establishing appropriate quality assurance frameworks; and (iii) transitioning to facilitating governance structures. Attention must also be paid to the science-policy-stakeholder interface. Better definition of industry’s role in contributing to science will improve credibility and legitimacy of the scientific process, and of resulting management.

Investigation of future climate change over the British Isles using weather patterns - James O. Pope; Kate Brown; Fai Fung; Helen M. Hanlon; Robert Neal; Erika J. Palin; Anne Reid (Climate Dynamics, 2022)
For those involved in planning for regional and local scale changes in future climate, there is a requirement for climate information to be available in a context more usually associated with meteorological timescales. Here we combine a tool used in numerical weather prediction, the 30 weather patterns produced by the Met Office, which are already applied operationally to numerical weather prediction models, to assess changes in the UK Climate Projections (UKCP) Global ensemble. Through assessing projected changes in the frequency of the weather patterns at the end of the 21st Century, we determine that future changes in large-scale circulation tend towards an increase in winter of weather patterns associated with cyclonic and westerly wind conditions at the expense of more anticyclonic, settled/blocked weather patterns. In summer, the results indicate a shift towards an increase in dry settled weather types with a corresponding reduction in the wet and windy weather types. Climatologically this suggests a shift towards warmer, wetter winters and warmer, drier summers; which is consistent with the headline findings from the UK Climate Projections 2018. This paper represents the first evaluation of weather patterns analysis within UKCP Global. It provides a detailed assessment of the changes in these weather patterns through the 21st Century and how uncertainty in emissions, structural and perturbed parameters affects these results. We show that the use of these weather patterns in tandem with the UKCP projections is useful for future work investigating changes in a range of weather-related climate features such as extreme precipitation.

Gimme Shelter: differential utilisation and propagule creation of invasive macrophytes by native caddisfly larvae - Kate Crane; Ross N. Cuthbert; Anthony Ricciardi; Louise Kregting; Neil E. Coughlan; Hugh J. MacIsaac; Neil Reid; Jaimie T. A. Dick (Biological Invasions, 2021)
In aquatic systems, invasive submerged macrophytes considerably alter the structure and functioning of communities, thus potentially compromising ecosystem services. The prolific spread of invasive macrophytes is often aided by vegetative fragment propagation, yet the contributions of various commonly occurring invertebrates to such fragmentation are often unquantified. In the present study, we examine fragmentary spread of invasive macrophytes by a group of shredder-herbivores, larval caddisflies. Through novel application of the comparative functional response (FR; resource use as a function of density) approach to the native case-building species Limnephilus lunatus , we compared utilisation of non-native waterweeds Elodea canadensis and E. nuttallii in mono- and polycultures. Furthermore, we quantified de-cased and cased caddisfly-induced fragment production and length changes among non-native E. canadensis , E. nuttallii , Crassula helmsii and Lagarosiphon major under two different plant orientations: horizontal (floating) versus vertical (upright) growth forms. Larval caddisflies exhibited Type II (hyperbolic) FRs towards both Elodea species, and utilised each plant at similar rates when plants were provided separately. When plant species were presented in combination horizontally, E. canadensis was significantly less utilised compared to E. nuttallii , corroborating observations in the field. De-cased larvae produced new plant fragments for all four aquatic macrophytes, whereas cased larvae fragmented plants significantly less. Elodea nuttalii and C. helmsii were fragmented the most overall. Crassula helmsii was utilised to the greatest extent when plants were horizontally orientated, and Elodea species when vertically orientated. This study identifies and quantifies a mechanism from a novel species group that may contribute to the spread of invasive macrophytes in aquatic systems. Whilst exploititative interactions are thought to impede invasion success, here we demonstrate how resource utilisation by a resident species may exacerbate propagule pressure from an invasive species.

Addressing Marine and Coastal Governance Conflicts at the Interface of Multiple Sectors and Jurisdictions - Manuel Bellanger; Cameron Speir; Fabian Blanchard; Kate Brooks; James R. A. Butler; Scott Crosson; Robert Fonner; Sophie Gourguet; Daniel S. Holland; Sakari Kuikka; Bertrand Le Gallic; Rebecca Lent; et al. (Frontiers in Marine Science, 2020)

The prevalence of plagioclase antecrysts and xenocrysts in andesite magma, exemplified by lavas of the Tongariro volcanic complex, New Zealand - Phil Shane; Kate Cocker; Alisha Coote; Claudine H. Stirling; Malcolm R. Reid (Contributions to Mineralogy and Petrology, 2019)

Tsunami runup and tide-gauge observations from the 14 November 2016 M7.8 Kaikōura earthquake, New Zealand - William Power; Kate Clark; Darren N. King; Jose Borrero; Jamie Howarth; Emily M. Lane; Derek Goring; James Goff; Catherine Chagué-Goff; James Williams; Catherine Reid; Colin Whittaker; et al. (Pure and Applied Geophysics, 2017)

Information infrastructure for Australia’s Integrated Marine Observing System - Marton G. Hidas; Roger Proctor; Natalia Atkins; Julian Atkinson; Laurent Besnard; Peter Blain; Philip Bohm; Jon Burgess; Kim Finney; Dan Fruehauf; Guillaume Galibert; Xavier Hoenner; et al. (Earth Science Informatics, 2016)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

An appraisal of microwave-assisted Tessier and BCR sequential extraction methods for the analysis of metals in sediments and soils - Miriam Katherine Reid; Kate L. Spencer; Laura Shotbolt (Journal of Soils and Sediments, 2011)

Signaling of neuronal cell death by the p75NTR neurotrophin receptor - Elizabeth J. Coulson; Kate Reid; Perry F. Bartlett (Molecular Neurobiology, 1999)